2014
DOI: 10.1111/jpn.12208
|View full text |Cite
|
Sign up to set email alerts
|

Presence and content of kynurenic acid in animal feed

Abstract: Kynurenic acid (KYNA) was found to be an antagonist of iontropic glutamate receptors and alpha7 nicotinic acetylcholine receptors. Furthermore, it was documented that KYNA is an agonist of G-protein coupled GPR35 receptors which are mainly present in the gastrointestinal tract. It was also found that KYNA is present in the gastrointestinal tract and that its concentration gradually increases along it. The origin of KYNA in the gastrointestinal tract is not known. Both might be synthesized from tryptophan in it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…KYNA has a key role in numerous biological species and their environment. The natural abundance of this biomolecule is essential in plants [19], in animal feed [20], in amphibians as pheromones [21] and moreover in fish as lymphocyte-activators [22] with potential aggravating properties [23].…”
Section: Resultsmentioning
confidence: 99%
“…KYNA has a key role in numerous biological species and their environment. The natural abundance of this biomolecule is essential in plants [19], in animal feed [20], in amphibians as pheromones [21] and moreover in fish as lymphocyte-activators [22] with potential aggravating properties [23].…”
Section: Resultsmentioning
confidence: 99%
“…The highest concentration of KYNA was found in feed for livestock, where it varied from 0.198 μg/g fresh weight to 0.414 μg/g fresh weight. Based on the measurement of KYNA content in feed ingredients, the authors concluded that the concentration of KYNA in animal feed was not controlled and deliberately set, but its final content depended on the ingredients used [ 84 ].…”
Section: Kynurenic Acid In Foodmentioning
confidence: 99%